Development of sensorless control drive for permanent magnet synchronous motor using a system-onprogrammable-chip - Nguyen Khanh Quang; Doan Duc Tung (My University, 2016)
Development of sensorless control drive for permanent magnet synchronous motor using a system-onprogrammable-chip
Keywords: Sensorless control; PMSM; System-on-Chip (SoPC)